Corporate entrepreneurship at RELX Group: How has the organization leveraged corporate venturing and acquisitions to accelerate its overall business strategy? - Hills, Oscar (2015)
How firms build new capabilities to adapt to changing environments is at the core of strategic management. Corporate venturing is an important component of this, however, research has neglected to acknowledge the criteria for success and how CV activities tie in to overall business strategy. In this study, I analyse the effectiveness of CV at RELX Group and describe how they have developed a capability to create and develop ventures through corporate venture capital and acquisitions. Central to this are the learning processes that enable the firm to build up an external corporate venturing capability by engaging in acquisitive learning. In this study of a number of corporate executives with experience in corporate venturing, certain criteria are presented that could help those corporations contemplating the initiation of acquisition or corporate start-up activities to effectively manage the inherent challenges.